A Pragmatic Inquiry into Adulation and Condemnation in Nigerian Diasporic Social Media Discourse - Jolaoso, Oluwafemi; Dairo, Nureni Abolanle (Journal of Language and Literature Studies, 2026)
This paper presents a pragmatic analysis of the social media discourses of Nigerians in the diaspora. The diaspora phenomenon has been a major theme of discussion and discourse on the African continent, and Nigeria presents a unique case. The paper employs a qualitative approach to attempt a pragmatic analysis of online discourses concerning Nigerians in the diaspora. The data were fifty (50) screenshots of posts by Nigerians in the diaspora sourced from Facebook and Twitter. The data were subjected to pragmatic analysis anchoring on Attribution theory to construe how Nigerian diasporic social media discourses are structured to project ascribing (attributing) justification for adulation and condemnation of Nigeria and their host countries. Findings reveal that Nigerians in the diaspora foreground condemnation of Nigeria as regards economic hardship, leadership failure, impunity and religious deceit and condemnation of the host countries in terms of racism practice, unfavourable weather, stress at work, scarcity of desired food items and unfavourable immigration laws. Adulation expressed about Nigeria concerns liveliness, local foods, communal life and cheap commodities while adulation about the host countries’ borders on availability of jobs, good standard of living, good leadership style, justice and access to quality social amenities. It is concluded that despite leaving Nigeria for other countries in search of a better life, Nigerians in the diaspora are not completely fulfilled as they still appreciate certain things and lifestyles about Nigeria wish they have no access to in their host countries and they express their dislike about their host countries which are communicated in their social media discourses. It is therefore concluded that there is no country that has all human needs and there is none that does not have anything desired.